1992
DOI: 10.1093/bja/69.6.589
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anaesthesia for Caesarean Section: Comparison of 22-Gauge and 25-Gauge Whitacre Needles With 26-Gauge Quincke Needles

Abstract: We have studied 150 women undergoing elective Caesarean section under spinal anaesthesia. They were allocated randomly to have a 22-gauge Whitacre, a 25-gauge Whitacre or a 26-gauge Quincke needle inserted into the lumbar subarachnoid space. The groups were compared for ease of insertion, number of attempted needle insertions before identification of cerebrospinal fluid, quality of subsequent analgesia and incidence of postoperative complications. There were differences between groups, but they did not reach s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 22 publications
(29 reference statements)
6
54
1
3
Order By: Relevance
“…The overall incidence of postdural puncture headache ranges from 0% to 37% as reported by various authors 25 30 , which closely resembles our study, demonstrated PDPH incidence of 20%, and 12.5% patients with 25G Quincke, and 27G Quincke needles respectively. Although frequency of PDPH was relatively higher in all the three groups in that study, it was again clearly observed that 27G Whitacre needle reduced the frequency of PDPH in patients undergoing Caesarean section.…”
Section: Discussionsupporting
confidence: 91%
“…The overall incidence of postdural puncture headache ranges from 0% to 37% as reported by various authors 25 30 , which closely resembles our study, demonstrated PDPH incidence of 20%, and 12.5% patients with 25G Quincke, and 27G Quincke needles respectively. Although frequency of PDPH was relatively higher in all the three groups in that study, it was again clearly observed that 27G Whitacre needle reduced the frequency of PDPH in patients undergoing Caesarean section.…”
Section: Discussionsupporting
confidence: 91%
“…However, some studies have shown no difference in PDPB related to the needle size and shape (7,11). The second hypothesis is that repeated spinal puncture attempts cause PDPB (16). However, some studies revealed this to be untrue.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-nine studies (16 RCT, [10][11][12]14,[16][17][18][19][20][21]23,24,26,[28][29][30] ten cohort studies, [33][34][35][36][38][39][40][41][42][43] and 13 case series 45,[47][48][49][50][51][53][54][55][56][57][58][59][60] ) contained data on frequency of ADP or PDPH (Table I). Figures 1 to 3 summarize the meta-analyses of ADP and PDPH risks for different epidural and spinal needles.…”
Section: Dp and Pdph Ratesmentioning
confidence: 99%